Ethylene oxide exposure, inflammatory indicators, and depressive symptoms: a cross-sectional study and mediation analysis based on a non-institutionalized American population - Du, Dongru; Yuan, Yanling; Guan, Xuan; Xie, Qinglian; Dong, Zaiquan (Frontiers in Public Health, 2024)
Background Ethylene oxide (EO) is a volatile compound positively correlated with respiratory and cardiovascular diseases. Currently, evidence suggests that environmental exposure may contribute to depressive symptoms. This study evaluated the correlation between EO exposure and depressive symptoms and investigated whether inflammatory indicators had a mediation effect on this correlation. Methods Patients were enrolled from the National Health and Nutrition Examination Survey during 2013–2016, and 2,764 (49.67% male and 50.33% female) participants were ultimately included. EO exposure was determined by measuring hemoglobin-EO adduct (Hb-EO) concentration due to its long half-life, which was log2-transformed. Depressive symptoms were assessed using the Patient Health Questionnaire-9. Multivariable logistic regression analysis was performed to identify any correlations before and after covariate adjustment. Sensitivity analysis, subgroup analyses, and interaction tests were performed to further evaluate identified correlations. Mediation analysis was conducted to reveal whether specific inflammatory indicators mediated the correlation. Results A high prevalence of depressive symptoms was observed in quartiles with increased levels of EO exposure, and male individuals exhibiting higher Hb-EO levels than female individuals. A positive correlation was observed between EO exposure and depressive symptoms (odds ratio [OR]: 1.439, 95% confidence interval [CI]: 1.310, 1.581), which remained stable even after covariate adjustment (OR: 1.332, 95% CI: 1.148, 1.545). Interaction tests showed significant effects of sex (p < 0.001) and thyroid diseases (p = 0.048) on this correlation. In the mediation analysis, white blood cell (p = 0.010) and neutrophil counts (p = 0.010) exerted a mediating effect, accounting for 13.6 and 11.9%, respectively. Conclusion Increased exposure to EO is associated with an elevated risk of depressive symptoms, where white blood cell and neutrophil counts exert a significant mediating effect. Further prospective studies are required to investigate the potential link among EO, other environmental pollutants, and human mental health.